Exploring Higher Education Students' Self-Efficacy: How Self-Efficacy Dimensions Influence Numeracy - Herra Aprillia Sabrina; Yoppy Wahyu Purnomo; Fery Muhamad Firdaus; Danuri (UIN Sunan Kalijaga Yogyakarta, 2024)
Numeracy is associated with students' self-efficacy, and it is crucial to examine the elements affecting numeracy proficiency, particularly behavior, including self-efficacy. A lack of research amalgamates both dimensions, encompassing the reciprocal impacts and the impact of contextual factors like gender and educational background. This study seeks to ascertain the influence of mathematics self-efficacy aspects on numeracy among elementary school teacher education students in the Yogyakarta region. The sampling method employed was non-probability sampling, specifically utilizing a convenience sampling methodology with a sample size of 215. The data analysis employed Structural Equation Modeling – Partial Least Squares (SEM–PLS). This study identifies the